Oocyte batch development and enumeration in the European anchovy (Engraulis encrasicolus) - FERRERI, R.; GANIAS, K.; GENOVESE, S.; FONTANA, I.; GIACALONE, G.; BONANNO, A.; MAZZOLA, S.; ARONICA, S.; MANGANO, S.; BASILONE, G. (Mediterranean Marine Science, 2016)
An alternative method to the traditional hydrated oocyte (HO) method has been evaluated for the Sicilian anchovy, Engraulis encrasicolus. The method is based on the processing of ovarian whole mount images and the identification of the spawning batch in oocyte size frequency distributions and shows the advantage that it can be applied to various oocyte stages rather than strictly to the HO stage. Despite the peculiar elliptical shape of anchovy oocytes, this image analysis technique was fully successful since the yolked stage appeared to perform equally to the HO stage for anchovy batch fecundity measurements.